A COMPARATIVE STUDY ON THE EFFECT OF NHT AND RSQC2 TECHNIQUES - Fitri Wulandari., M.Pd (Bajang Institute, 2021)
The aims of this research are to investigate whether there is any significant difference on reading comprehension between students who were taught using NHT and those who were taught using RSQC2 techniques and, to determine which one of the two techniques is more effective in improving students’ reading comprehension. The research design used in this study was Pre-test and Post-test Comparison Group Design. The samples were three classes of the tenth grade students at SMKN 6 Pekanbaru of the 2015 academic year. The samples were selected using the technique of cluster sampling. The total samples were 97 students. The forms of the test were multiple choices. Finally, first the writer found that significant probabilities was higher than 0.05 (sig > 0.05) in multiple comparison one way ANOVA. It means that there is no significant difference on students’ reading comprehension between using NHT and RSQC2 techniques are good in comprehending reading text at SMKN 6 Pekanbaru. The second, found that significant probabilities was lower than 0.05 (sig > 0.05) in both paired sample t-test and independent sample t-test. It means that there is a significant difference of students’ reading comprehension pre-test and post-test of experimental classes